2022
DOI: 10.1097/md.0000000000029579
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain in the emergency department: From score to core—A prospective clinical study

Abstract: High-sensitivity troponin assay brought new challenges as we detect elevated concentration in many other diseases, and it became difficult to distinguish the real cause of this elevation. In this notion, diagnosis of acute coronary syndrome (ACS) remains a challenge in emergency department (ED). We aim to examine different approaches for rule-in and rule-out of ACS using risk scores, copeptin, and coronary computed tomography angiography (CCTA). A prospective observational study was designed to evaluate chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…At the same time, a combined approach including CCTA and copeptin provides the highest power for ruling out an ACS (AUC 0.772, p <0.001), superior to hc-sTn, risk scores, or any other test. 22 In another study, patients with suspected ACS in whom AMI has been excluded based on hs-cTn values, underwent CCTA following AMI rule-out, to identify the presence of CAD. The authors demonstrated that CAD was 3 times more likely in patients who had slightly elevated levels of hs-cTnI compared to those with low values of serum hs-cTnI, indicating that CCTA added to routine hs-TnI determination could improve the diagnosis of chronic coronary syndromes in patients presenting to the ED for chest pain.…”
Section: Ccta and Cardiac Biomarkers In The Edmentioning
confidence: 99%
“…At the same time, a combined approach including CCTA and copeptin provides the highest power for ruling out an ACS (AUC 0.772, p <0.001), superior to hc-sTn, risk scores, or any other test. 22 In another study, patients with suspected ACS in whom AMI has been excluded based on hs-cTn values, underwent CCTA following AMI rule-out, to identify the presence of CAD. The authors demonstrated that CAD was 3 times more likely in patients who had slightly elevated levels of hs-cTnI compared to those with low values of serum hs-cTnI, indicating that CCTA added to routine hs-TnI determination could improve the diagnosis of chronic coronary syndromes in patients presenting to the ED for chest pain.…”
Section: Ccta and Cardiac Biomarkers In The Edmentioning
confidence: 99%